BACTERIOLOGICAL ASSESSMENT OF SOME COMMERCIALLY SOLD YOGHURT IN UTURU, ABIA STATE, NIGERIA: A PRELIMINARY STUDY - Ekeleme, U. G.; Mohammed, A. (FUDMA Journal of Sciences, 2024)
A preliminary study was carried out to determine the bacteriological quality of commercial yogurt sold in Uturu, Abia State, Nigeria. This involved isolation, characterization and antibiotics susceptibility of bacteria isolated from some commercially sold yoghurt in Uturu. Five different brands of yoghurt coded A to E were microbiologically analyzed using standard microbiological methods. The total viable count ranged from 0.9×102 cfu/ml – 2.0x103 cfu/ml, coliform count ranged from 0.4×102 cfu/ml – 1.0×103 cfu/ml, total staphylococcal count ranged from 1.1×101 to 1.8×102. Bacterial isolated include Staphylococcus species, Streptococcus species, Bacillus species and Lactobacillus species. The antibiotics susceptibility pattern of the bacterial isolates proved that drovid had the highest zones of inhibition from 31.8±1.2 mm to 36.1±0.3 mm, followed by oflaxacin (29.5±0.1 mm to 35.0±0.8 mm). The presence of coliform and Staphylococcus in the yoghurt may be as a result of unclean water used in the production, contaminated milk and unhygienic condition of the handlers. It is recommended that yoghurt producers, sellers and handlers should ensure a high level of hygiene and avoid long exposure of yoghurt before selling to consumers.